Use Of Commercial Feeding Formula Among Urban Children In Nagpur - Ambadekar Nithin N; Khandait Devendra W; Sanjay P; Vasudeo N.D (Wolters Kluwer Medknow Publications, 1999)
Research question: 1. What is the prevalence of use of commercial feeding formula (CFF) by mothers of underthree children attending Urban Health Training Center, G.M.C. Nagpur? 2. What are the practices regarding use of CFF? Objective: 1. To assess the prevalence of use of CFF. 2. To study the practices regarding the use of CFF. 3. To study some factors associated with use of CFF. Study design : Clinic based study. Setting: Urban Health Training Centre (UHTC), Govt. Medical College, Nagpur. Participants : Consecutive 600 underthree children and their mothers attending Urban Health Training Centre. Statistical analysis: Chi- square test, Z-test. Result : Prevalence of use of CFF was found to 43%. Out of 258 mothers who were using CFF . 65.11% were reconstituting the feed improperly , while 70.54% mothers were not taking proper hygienic precautions. In 80.62% cases, the practice was because of influence and advice by friends and private practitioners. Though use of CFF was more among higher socio-economic strata and higher literacy status. fairly large proportion of mothers from lower socio- economic strata and with less education were using CFF. Significantly more children fed with CFF were malnourished and also complained more about diarrhoeal diseases. Conclusion: Use of CFF is quite prevalent among urban mothers, moreover, better educational status and poverty does not have restraint on its use. Hence, specific educational programme should be developed to educate target group which would include medical professionals, mothers and even the general public from all strata of society.